2018
DOI: 10.1177/0021998318755866
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis and theoretical predictions of the tensile-strength retention of glass fiber-reinforced polymer bars based on resin type

Abstract: This paper presents experimental investigation, statistical analysis, and theoretical predictions of tensile-strength retention of glass fiber-reinforced polymer bars, made with vinyl-ester, polyester, or epoxy resins. The durability of glass fiber-reinforced polymer bars was evaluated as a function of time of immersion in alkaline solution. The aging of the three glass fiber-reinforced polymer bar types consisted of immersion glass fiber-reinforced polymer bar samples in an alkaline solution (up to 5000 h) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…e most commonly used glass and matrix materials were E-glass and vinylester, with 90 and 74% of the conducted research having used this fiber and matrix, respectively, as shown in Figure 2. Epoxy, on the other hand, has been only recently employed as the resin of GFRP reinforcing bars, with 14% of published work having explored its combination with E-glass [8,10,11,23,41,42]. e diameter has also been varied between 8 and 44.5 mm, with the majority being approximately 12 mm.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…e most commonly used glass and matrix materials were E-glass and vinylester, with 90 and 74% of the conducted research having used this fiber and matrix, respectively, as shown in Figure 2. Epoxy, on the other hand, has been only recently employed as the resin of GFRP reinforcing bars, with 14% of published work having explored its combination with E-glass [8,10,11,23,41,42]. e diameter has also been varied between 8 and 44.5 mm, with the majority being approximately 12 mm.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…In fact, elevated temperatures could accelerate the degradation induced by conditioning. As a result, the limits were found to be [37] 432-1478 41.9-60. x x 150 to 450 20 to x [11] x x 150 to 450 20 to 25 [12] x X Up to 1445 -20-65 [13] x 60 to 180 23 to x [14] x x 60 to 240 23 to x [15] x 100 to 660 40 x [23] x 41.67 to 208. 33 22 to x [42] x 90 to 365 23 to x [24] x 90 60 x [25] x 0.0208 to 0.1285 −100 to 325 x [26] x x 60 to 365 23 to x [27] x 30 to 180 23 to x [28] x 30 to 270 23 0-25 [29] x x x x 28 to 50 60 to x [30] x x x 180 to 540 23 to x [31] x 30 to 720 60 x [32] x 0.0417 to 0.125 100 to 300 x [33] x x x 90 to 730 60 20 & x 2 [34] x x 60 to 240 23 to 20-80 [35] x x 30 to 120 20 to 19-29 [36] x x x 30 to 132 −25 to 80 x [37] x x x 180 to 540 23 to x [38] x inappropriate and required revision through further research data.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations